1992
DOI: 10.1002/ijc.2910500109
|View full text |Cite
|
Sign up to set email alerts
|

Stefins and lysosomal cathepsins B, L and D in human breast carcinoma

Abstract: In the study of 50 matched pairs of breast carcinoma and normal breast tissue, the activities of cysteine proteinases (CPs), cathepsin (Cat) B and Cat L in tumors were increased on average by 18.5-fold and 52.5-fold respectively. The differences in activity of cysteine proteinase inhibitors (CPIs) between tumor and control breast tissues was also observed: in approximately two thirds of carcinomas, lowered CPI activity was measured (group-I patients), while similar or higher tumor CPI activity was measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 27 publications
2
69
0
1
Order By: Relevance
“…At this point, the crucial question is whether the observed relations in cystatin C levels influenced the total intracellular proteolytic potential in the two groups. It has been shown that alterations in total inhibitory activity of cysteine proteinase inhibitors or in protein level in case of stefin A were present in malignant tissue and normal parenchyma of the breast (Lah et al, 1992 and lung (Knoch et al, 1994). In the study by Lah et al (1992), lowered cysteine proteinase inhibitor activity in breast carcinoma tissue (i.e., in the low-activity group) was associated with significantly higher increases of cathepsin B and cathepsin L activities than those measured in the high-activity group, indicating higher proteolytic potential in the former group.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, the crucial question is whether the observed relations in cystatin C levels influenced the total intracellular proteolytic potential in the two groups. It has been shown that alterations in total inhibitory activity of cysteine proteinase inhibitors or in protein level in case of stefin A were present in malignant tissue and normal parenchyma of the breast (Lah et al, 1992 and lung (Knoch et al, 1994). In the study by Lah et al (1992), lowered cysteine proteinase inhibitor activity in breast carcinoma tissue (i.e., in the low-activity group) was associated with significantly higher increases of cathepsin B and cathepsin L activities than those measured in the high-activity group, indicating higher proteolytic potential in the former group.…”
Section: Discussionmentioning
confidence: 99%
“…The level of cathepsin B expression is elevated in human breast and ovarian cancers (Woynarowska et al, 1989;Gabrijelcic et al, 1992;Lah et al, 1992), and in several metastatic cell lines, including ras-transformed NIH 3T3 cells and Lewis lung carcinoma cells, in which the level of expression has been correlated with the increased malignancy (Brodt et al, 1992;Chambers et al, 1992). In many malignant cell lines, the enzyme is localized to the plasma membrane and is clearly secreted in most instances (Sloane et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The ECM contains several specific protease inhibitors, including members of the family of tissue inhibitors of metalloprotease [56], plasminogen activator inhibitor [57,58]. cystatin and stefin families [59,60]. The balance between the relative level of proteases and their specific inhibitors dictates the degree of protease activity, and essentially ensures that uncontrolled proteolysis of the components of the basement membrane does not occur.…”
Section: The Integrinsmentioning
confidence: 99%